The Use of List-Group-Label (LGL) Strategy in Teaching Vocabulary (A Pre-Experimental Research to the second semester Students of Islamic Education Department of Teacher Training and Education Faculty of IAIN Pontianak in the Academic Year of 2017/2018) - Sulaiman Sulaiman (Faculty of Economics, Law, and Humanities, 2019)
The aim of this research was to find out the effectiveness of List-Group-Label (LGL) strategy in teaching vocabulary and how significant the effect of List-Group-Label (LGL) strategy was in teaching vocabulary to the second semester Students of Islamic Education Department of Teacher Training and Education Faculty of IAIN Pontianak in the Academic Year of 2017/2018.The research design employs a pre-experimental research in form of one group Pretest- Posttest design and had no control group. The population of this research was all of the second semester Students of Islamic Education Department of Teacher Training and Education Faculty of IAIN Pontianak in the Academic Year of 2017/2018 consisted of 317 students and the chosen sample was class B. The sample was taken by apllying Cluster random sampling technique. The research was conducted at IAIN Pontianak.The technique of data collection in this research was measurement. The data were collected with essay test. The pre-test and post-test were distributed in order to get the data from the students. The data were analyzed by using t test. The result revealed that List-Group-Label (LGL) strategy was effective on students’ vocabulary mastery because the mean score in pretest and posttest were different and the difference were considered significant. The effect size calculation revealed that List-Group-Label (LGL) strategy gave strong effect to the students’ vocabulary mastery. It could be inferred that List-Group-Label (LGL) strategy was significantly effective in teaching vocabulary to the second semester Students of Islamic Education Department of Teacher Training and Education Faculty of IAIN Pontianak in the Academic Year of 2017/2018 and the treatments gave strong effect to the students in learning vocabulary. List-Group-Label (LGL) strategy can be implemented in teaching vocabulary in order to improve students’ vocabulary mastery.